Improving MoWaS Application Backbone System for The Effectiveness of Responsive Behaviour in Facing Crime Threats and Emergency Situations - Arif Arizal; Syariful Alim (Universitas Muhammadiyah Malang, 2017)
MoWaS is a mobile-based supporting application aiming to improve the rapid response against crime crime and emergency situations. The evaluation of MoWaS version 1.0 has 3 flaws. First, it is unable to create a group. Second, the MoWaS version 1.0 application is able to detect the current location of the alert sender but there is no feature to display information about nearby MoWaS application users. Third, MoWaS application version 1.0 is also not integrated with the official service or government agency related to the types of occurring crime. The results of the design revision and analysis were made including the MoWaS system architecture design, the MoWaS system flow described in the form of flowchart, and the MoWaS system interface design. The results of the analysis and design of MoWaS backbone system can be used as the basis for improvement of MoWaS system development. Hence, it can be concluded that the MoWaS application version 2.0 has a better work system than the previous version.